One‐pot synthesis of multifunctional electrocatalyst for hydrogen evolution, oxygen evolution and oxygen reduction. Issue 21 (11th September 2020) - Xu, Zejun; Zhang, Quan; Li, Min; Luo, Fang; Liu, Yanan; Wang, Ruitong; Ma, Xu; Yang, Zehui; Zhang, Daohong
Abstract: In this work, we report a facile method to prepare P, N co‐doped porous carbon (PNPC) by the carbonization of covalent organic polymer (COP) used as efficient metal‐free electrocatalyst for hydrogen evolution reaction (HER), oxygen evolution reaction (OER) and oxygen reduction reaction (ORR). Overpotential is only 150 mV for the PNPC electrocatalyst to reach 10 mA cm −2 in the acidic medium due to the heteroatom dopants in the carbon matrix; meanwhile, stable HER activity is recorded during 5000 potential cycles. Additionally, overpotential is 343 mV for PNPC electrocatalyst to drive OER catalysis with 10 mA cm −2, which is comparable to the benchmarked IrO2 (320 mV). Similarly, PNPC electrocatalyst can achieve a Pt‐like ORR catalytic activity. The power density of the assembled rechargeable zinc‐air battery (ZAB) is 1.8 times higher than that of the commercial system (Pt/C−IrO2 ) and charge‐discharge voltage gap is well maintained during 20 h test, implying the high stability of the formed PNPC electrocatalyst. Abstract : Electrocatalysis : P, N co‐doped porous carbon (PNPC) derived from covalent organic polymer shows high catalytic activities toward HER, OER and ORR due to the heteroatom dopants as well as porous structure. The assembled rechargeable zinc‐air battery exhibited 1.8 fold better performance than commercial Pt/C−IrO2 system. Additionally, PNPC required a low overpotential of 150 mV to drive HER catalysis in acidic medium.